Evaluation of CRYSTALS-Kyber and Saber on the ARMv8 architecture - Ortiz, Jheyne N.; Carvalho Rodrigues, Félix; Gazzoni Filho, Décio; Teixeira, Caio; López, Julio; Dahab, Ricardo (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2022)
This paper presents preliminary experimental results for the implementation of the third-round NIST finalists CRYSTALS-Kyber and Saber on the ARMv8 architecture. Our implementation uses NEON instructions to speed up key generation, encapsulation, and decapsulation of the reference codes. The benchmarks are performed on three devices: an Orange Pi WinPlus (Cortex-A53), a Raspberry Pi 4 (Cortex-A72), and a MacBook Air based on an Apple M1 chip. The experimental results show substantial improvements for Kyber and Saber, with speed-ups in the ranges 1.16-1.38x and 1.21-1.96x, respectively. We focused on the most time-consuming operations of each cryptosystem; however, similar works suggest that more expressive speed-ups can be obtained by extending the use of NEON instructions to other primary sub-routines.